'Response to Stanley Cavell's The World Viewed' - Paul Jenner (2015)
Stanley Cavell’s The World Viewed: Reflections on the Ontology Film (1979 [1971]) is patient with the ways in which common sense is threatened by our experience of film. The book offers a perspective rather than an overview, foregrounding its own conditions – working mostly from the memory of films, for instance, and seeking to focus Cavell’s sense of a discontinuity in his moviegoing experience. Questions of cinematic ontology, held at an experiential level, join a broad philosophical-historical narrative concerning our lack of presentness to the world. Both of these strands develop preoccupations and discoveries found in Cavell’s reception of ordinary language philosophy. Disclosing the contours of the cinematic through juxtapositions with other media, in ways evoking both medium-specific and post-medium concerns, Cavell’s study of film further establishes the reach of his key term, ‘acknowledgment’.